The Influence of Teacher-Student Relationship on Teaching Evaluation from the Perspective of Students - Huang, Yanman (Journal of China-ASEAN Studies, 2023)
Good teacher-student relationship is helpful to achieve educational goals and improve teaching quality. The research carried out a "Questionnaire Survey on teacher-student relationship and Teaching Evaluation of College C" on the prominent problems of teacher-student relationship in Chinese colleges and universities, and used descriptive statistics and multiple linear regression methods to discuss the types of teacher-student relationship in ideal and reality, the main ways of communication and satisfaction of students and their impact on teaching evaluation. First, we should take measures to build a new teacher-student relationship from the perspectives of universities, teachers and students. Second, in the construction of teaching evaluation system, improve the content of teaching evaluation; Establishment of teaching evaluation and feedback promotion joint mechanism; Establish a two-way interactive virtuous cycle mechanism of teacher-student relationship and teaching evaluation.